STRATEGI PENGEMBANGAN USAHA DALI NI HORBO PADA PELAKU USAHA DI KABUPATEN TAPANULI UTARA - Ulidesi Siadari; Rikardo Silaban; Ade Maya Mei Shanty; Agusta Linda Nora; Diana Sari Harahap; Pertama Yul Asmara Pane (COVIT (Community Service of Health), 2023)
Regional or culinary specialties are one of the attractions for visitors or tourists who will visit. Dali ni horbo is one of the regional specialties in the North Tapanuli Regency. Dali ni horbo is made from buffalo milk. Dali ni horbo is cooked in the traditional way and uses pineapple juice as a thickening agent. In other areas in North Sumatra, there are also those who use papaya leaf extract and alo-alo as a thickening agent. Dali ni Horbo is sold in the market by traders only packaged using plastic. Simple processing methods and simple packaging methods are obstacles for Dali ni Horbo traders which causes the shelf life of Dali ni Horbo to be short, and the supply of raw materials (buffalo milk) to make Dali ni Horbo is still relatively difficult to obtain. Thus, several product innovations and the development of marketing strategies are needed so that more and more people know about Horbo Dali Ni so that the demand for Horbo Dali Ni will increase. Keywords: Dali Ni Horbo (Buffalo Milk), Culinary, Business Model, Marketing